BUSINESS PERFORMANCE OF DUCK FARMERS IN BREBES REGENCYCENTRAL JAVA - Sumekar, W.; Isbandi, I.; Atmomarsono, U.; Susilowati, I. (Diponegoro University, 2013)
The duck farmers in Brebes Regency has not been able to deal with the business dynamics with themain problems in feed and Day Old Duck (DOD).The aim of the research was to analyze the businessperformance of duck farmer in Brebes Regency. The technical and economical efficiency was calculatedto find out the status of duck farmer’s business performance. The research was conducted to four mostactive duck farmer groups (KTTI) in Brebes Regency. The research was done based on survey methodwith 123 duck farmers of the group member as the respondents. The research results show that not all ofthe duck farmers performed their business efficiently (the average technical efficiency is 0.9981) sincethe number of duck ownership, forage, and the use of technology were not optimum yet. The return toscale value of the duck farming businesses was 1.0868, which showed the presence of opportunity toincrease production. This research recommends that it is necessary to manage the productionmanagement in order to increase business performance by optimizing the number of duck ownership,forage feed, and the use of technology.